Global Governance and International Cooperation: Managing Global Catastrophic Risks in the 21st Century - Richard Falk; Augusto Lopez-Claros (Routledge, 2024)
The Global Governance Forum and the Global Challenges Foundation collaborate in this collection in their concern that the UN Charter and the contemporary infrastructure for international cooperation are no longer fit for purpose and lack the instruments, resources and legitimacy to address the catastrophic risks threatening our future. Twenty-eight contributors offer thoughtful proposals for reforming existing international institutions and creating new ones to build a more peaceful, prosperous and just world, covering themes such as the management of weapons of mass destruction, collective security arrangements, justice and equity in economics, human rights, migration and refugees, climate mitigation, and food security, all bearing on the health of both people and planet. The vital project of this century is building institutions that will underpin global governance in coming decades, requiring imagination, persistence, empathy, and confidence that we will find a path to enhanced mechanisms of binding international law and the resources to make that happen. The volume is essential reading for scholars and researchers on international politics and public policy and indispensable for diplomats and government agencies.
Keywords: 320; global governance; united nations